2010
DOI: 10.1097/hjh.0b013e328333fe4d
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal blood pressure and progression to end-stage renal disease or death in nondiabetic chronic kidney disease stages 3 and 4

Abstract: Glomerular filtration rate and nocturnal SBP values, but not nondipper pattern, were associated with risk to develop ESRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 22 publications
0
37
2
1
Order By: Relevance
“…In a recent study, Redon et al 25 have shown that the prevalence of non-dippers in patients with stages 3 or 4 chronic kidney disease was 47%, far below our 72.1% observation. Possible explanations include an office BP considerably lower in the former study and differences in the methodology for diagnosing the dipping status with regard to the nighttime period definition.…”
Section: Circadian Bp Variation and Risk Categoriescontrasting
confidence: 81%
See 1 more Smart Citation
“…In a recent study, Redon et al 25 have shown that the prevalence of non-dippers in patients with stages 3 or 4 chronic kidney disease was 47%, far below our 72.1% observation. Possible explanations include an office BP considerably lower in the former study and differences in the methodology for diagnosing the dipping status with regard to the nighttime period definition.…”
Section: Circadian Bp Variation and Risk Categoriescontrasting
confidence: 81%
“…Possible explanations include an office BP considerably lower in the former study and differences in the methodology for diagnosing the dipping status with regard to the nighttime period definition. 21,25 In summary, high-risk hypertensives show a remarkable high prevalence of abnormalities in circadian BP variation with a key influence in absolute levels of nighttime and 24-h BP. These observations support the recommendation of a wider use of ABPM in high-risk hypertensive patients.…”
Section: Circadian Bp Variation and Risk Categoriesmentioning
confidence: 99%
“…In CKD patients, non-dipping was found to be associated with poor renal outcomes, 13,14 but other studies report no relationship. 15, 17 Additionally, in people with preserved kidney function, one study reported a significant association of non-dipping with deterioration of kidney function, 28 but another study did not. 16 High nocturnal BP is, in some cases, accompanied by a non-dipping pattern, but both patterns are not always present together and there are differences in the significance between nocturnal BP and the non-dipping pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Redon et al reported a greater risk for progression to ESRD in patients with night-time SBP higher than 130 mmHg in nondiabetic patients at CKD stages 3 and 4. 17 Another study reported that night-time SBP levels enabled more accurate prediction of renal and cardiovascular risk than daytime SBP levels in patients with CKD stages 2-5. 14 Nevertheless, whether night-time SBP is superior to daytime SBP has not been fully investigated in the general CKD patient population.…”
Section: Measurement Of Abpmmentioning
confidence: 99%
See 1 more Smart Citation